PAPR reduction of OFDM signal by use of DSI method with time-frequency domain swapping algorithm - Boonsrimuang, Pisit; Naito, Katsuhiro; Mori, Kazuo; Paungma, Tawil; Kobayashi, Hideo (My University, 2007)
The main disadvantage of orthogonal frequency division multiplexing (OFDM) is the high time domain PAPR. The larger PAPR signal would fatally degrade BER performance in non-linear channels. This paper proposes an improved DSI method, which can achieve better PAPR and BER performances in the non-linear channel with less computation complexity than the conventional DSI method. The feature of proposed method is to employ the time-frequency domain swapping algorithm in the determination of frequency data for dummy sub-carriers. This paper presents various computer simulation results to verify the effectiveness of proposed DSI method. Copyright © 2007 The Institute of Electronics, Information and Communication Engineers.
Keywords: Dummy sub-carriers; Non-linear amplifier; OFDM; PAPR